Plankton biodiversity in various typologies of inundation in Paminggir peatland, South Kalimantan, Indonesia on dry season - Dini Yunandar; HEFNI EFFENDI; WIDIATMAKA; YUDI SETIAWAN (Society for Indonesian Biodiversity, 2020)
Abstract. Yunandar, Effendi H, Widiatmaka, Setiawan Y. 2020. Plankton biodiversity in various typologies of inundation in Paminggir peatland, South Kalimantan, Indonesia on dry season. Biodiversitas 21: 1012-1019. The aim of the study was to analyze the typology of inundation areas and plankton biodiversity in Paminggir peatland, South Borneo, Indonesia. Typology of inundation was determined by image processing and spatial analysis using supervised classification method from Landsat 1994, 2014, 2019. Plankton biodiversity was determined using purposive sampling in detected inundation from spatial analysis. Some environmental factors like temperature, Ph and DO were also analyzed. Confirmation of the results of spatial analysis of peatland typology made from overall accuracy and Kappa informed 88.48% and 0.8. The typology of permanent inundation decreased by 30% from 1994 to 2019 during the dry period from June to August of the total study area of 43275,584 hectares due to sedimentation, land conversion for settlement, and increase in water weeds. Inundation criteria with duration throughout the year were was categorized as permanent, whereas temporary inundation was tentative even in certain dry season. Plankton index biodiversity in permanent inundation was more varied compared to temporary inundation. Phytoplankton from the freshwater Chrysophyta group was more dominant, while zooplankton from the Nauplius group, which were the natural food for fish larvae always presented in the typology of permanent inundation.